Perancangan Aplikasi Pemantau Harga Cryptocurrency Secara Realtime Berbasis Android Dengan Menggunakan Metode Prototype - Suhardi; Sofyan Mufti Prasetiyo (OKTAL : Jurnal Ilmu Komputer dan Sains, 2022)
Along with the development of technology in the field, people's needs for speed, economic convenience and security of financial transactions using Virtual Currency or virtual currencies are increasing. This technology will allow people to find out information about Cryptocurrencies either to invest without the intervention of banks or other financial institutions. Cryptocurrency is a digital or virtual currency that uses cryptography for security and is difficult to counterfeit. Heavy applications make it difficult for users or users to find out Cryptocurrency prices in Realtime. By using the Prototype method coupled with the API, this application can be accessed easily, without the need for a programming process and a lot of requests so that the size and speed of the application will be very light and the time required for application development is relatively shorter and in the application there is a cryptocurrency graph. and cryptocurrency coin info which can be used to pool and compare cryptocurrency prices. The application is designed and created using Android Studio 4.2.1, SDK Android 10.0 (API 29) with API sourced from coinmarketcap as a medium for retrieving prices in real time, and there is media for finding information such as graphs, statistics, coin info, about cryptocurrencies and knowledge of cryptocurrencies. From the research results, it is hoped that the application can help users/users find cryptocurrency information and compare and compare Cryptocurrency prices in real time and easily.